Harmonizing Faith: Exploring the Uniformity of Jum’at Sermons in Malaysia (A Study Analysis of Religious Discourse Dynamics) - Abdul Matin Bin Salman; Fuad Muhammad Zein; Joko Robby Prasetyo (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This abstract aims to elucidate the phenomenon of Friday sermon uniformity in Malaysia, revealing its intricate relationship with religion and power. Employing a qualitative approach, this study utilizes interviews and document analysis to uncover the mechanisms behind sermon uniformity. It is found that this practice, rooted in the Malaysian Islamization Program, has evolved into a national discourse, serving as a conduit for government messaging and propaganda. Furthermore, the study illuminates the role of religious authorities, particularly within the monarchy, in shaping and enforcing sermon uniformity. It underscores how the convergence of religious and political agendas is reflected through standardized sermon content, emphasizing the influence wielded by these authorities in upholding religious and cultural norms. Through its findings, this research provides valuable insights into the complex power dynamics within Malaysia's religious landscape, prompting further reflection on the implications of such uniformity in a diverse and democratic society.